How monstrous is grendel - Marín Quizhpi, Elizabeth
In the last few years, Beowulf has leapt from academic obscurity into the public imagination. A new translation of the ancient poem and two feature films are showing the world that English literature did not begin with Shakespeare. Even the Lord of the Rings films reminded us that Tolkien did not create his fantasy out of whole cloth - Beowulf was one of his main sources. In this thesis, we will attempt to describe some of the different kinds of Grendels that have been created, and compare them to the original Grendel of the Epic work from which they were derived. The thesis starts with the Old English poem Beowulf, the story and its history from the time of its creation up to the present. This epic poem has all the standard ingredients, including a heroic character in the form of Beowulf who performs superhuman deeds, championing good against evil. Then the thesis refers to Grendel: Grendel in Literature and in films. First, the Grendel in the Old English poem is described; then Grendel by John Gardner; later, the Grendel in Beowulf y Grendel, directed by Sturla Gunnarsson is depicted and finally, the Grendel in Beowulf, directed by Robert Zemeckis is analyzed. Both films share certain themes; the coming of Christianity to Denmark; the futility of revenge; characters who rip off their own arms; and the power of beautiful women. Some films change the very nature of its hero, Beowulf too. At the end of the thesis, the differences between Grendel in the original poem Beowulf and Grendel in some modern film adaptations is pointed out